Species diversity of the family Lecithoceridae (Lepidoptera: Gelechioidea) in the Philippine Islands, with descriptions of three new species of Torodora Meyrick. (3rd July 2019) - Park, Kyu-Tek
ABSTRACT: The Lecithoceridae of the Philippine Islands are reviewed, including details of the genera and a check list of the known species. Type localities, depositories of types, geographic distributions, diagnostic key characters and historical records are given for each species. Three new species of Torodora Meyrick are described and illustrated: T. rhaphisodes Park, sp. nov., T. mindoroensis Park, sp. nov. and T. samarensis Park, sp. nov. Thubana fangensis Park 2003 is reported for the first time from the Philippines. http://www.zoobank.org/urn:lsid:zoobank.org:pub:E28167C2-AAAD-474F-A553-8F8F0CC2F471